A 3D model of ovarian cancer cell lines on peptide nanofiber scaffold to explore the cell–scaffold interaction and chemotherapeutic resistance of anticancer drugs - Zehong Yang (Dove Medical Press, 2011)
Zehong Yang1, Xiaojun Zhao1,21Nanomedicine Laboratory, West China Hospital and Institute for Nanobiomedical Technology and Membrane Biology, Sichuan University, Chengdu, People’s Republic of China; 2Center for Biomedical Engineering, Massachusetts Institute of Technology, Cambridge, MA, USAAbstract: RADA16-I peptide hydrogel, a type of nanofiber scaffold derived from self-assembling peptide RADA16-I, has been extensively applied to regenerative medicine and tissue repair in order to develop novel nanomedicine systems. In this study, using RADA16-I peptide hydrogel, a three-dimensional (3D) cell culture model was fabricated for in vitro culture of three ovarian cancer cell lines. Firstly, the peptide nanofiber scaffold was evaluated by transmission electron microscopy and atom force microscopy. Using phase contrast microscopy, the appearance of the representative ovarian cancer cells encapsulated in RADA16-I peptide hydrogel on days 1, 3, and 7 in 24-well Petri dishes was illustrated. The cancer cell–nanofiber scaffold construct was cultured for 5 days, and the ovarian cancer cells had actively proliferative potential. The precultured ovarian cancer cells exhibited nearly similar adhesion properties and invasion potentials in vitro between RADA16-I peptide nanofiber and type I collagen, which suggested that RADA16-I peptide hydrogel had some similar characteristics to type I collagen. The precultured ovarian cancer cells had two-fold to five-fold higher anticancer drug resistance than the conventional two-dimensional Petri dish culture. So the 3D cell model on peptide nanofiber scaffold is an optimal type of cell pattern for anticancer drug screening and tumor biology.Keywords: 3D culture, anticancer drug, nanofiber scaffold, cell viability, ovarian cancer